Influence of Plant Growth Regulators on Growth, Flowering and Yield of Chrysanthemum (Dendrathema Grandiflora Tzvelev) CV. ’IIHR-6’ - M.U. Navale; S.A. Aklade; J.R. Desai; P.V. Nannavare (International Journal of Pharma and Bio Sciences, 2010)
An experiment was carried out at Floriculture Research Scheme, ASPEE college of Horticulture and Forestry, NAU, Navsari during the winter season of the year 2006-07 to study the effect of plant growth regulators on growth, flowering and yield of chrysanthemum cv. ‘IIHR-6’. The results revealed that plant sprayed with MH at 1250 mg/l recorded the maximum reduction in plant height with maximum number of branches, plant spread, shelf life and vase life of flowers, whereas it was also found beneficial for delaying and increasing the duration of flowering. However, in case of flower yield per plant and per hectare, the lower concentration of MH at 750 mg/l was found significantly superior as compared to other treatment.